Unveiling the Mechanisms of a Remission in Major Depressive Disorder (MDD)-like Syndrome: The Role of Hippocampal Palmitoyltransferase Expression and Stress Susceptibility - Careen A. Schroeter; Anna Gorlova; Michael Sicker; Aleksei Umriukhin; Alisa Burova; Boris Shulgin; Sergey Morozov; Joao P. Costa-Nunes; Tatyana Strekalova (Biomolecules)
Post-translational modifications of proteins via palmitoylation, a thioester linkage of a 16-carbon fatty acid to a cysteine residue, reversibly increases their affinity for cholesterol-rich lipid rafts in membranes, changing their function. Little is known about how altered palmitoylation affects function at the systemic level and contributes to CNS pathology. However, recent studies suggested a role for the downregulation of palmitoyl acetyltransferase (DHHC) 21 gene expression in the development of Major Depressive Disorder (MDD)-like syndrome. Here, we sought to investigate how susceptibility (sucrose preference below 65%) or resilience (sucrose preference > 65%) to stress-induced anhedonia affects DHHC gene expression in the hippocampus of C57BL/6J mice during the phase of spontaneous recovery from anhedonia. Because MDD is a recurrent disorder, it is important to understand the molecular mechanisms underlying not only the symptomatic phase of the disease but also a state of temporary remission. Indeed, molecular changes associated with the application of pharmacotherapy at the remission stage are currently not well understood. Therefore, we used a mouse model of chronic stress to address these questions. The stress protocol consisted of rat exposure, social defeat, restraint stress, and tail suspension. Mice from the stress group were not treated, received imipramine via drinking water (7 mg/kg/day), or received intraperitoneal injections of dicholine succinate (DS; 25 mg/kg/day) starting 7 days prior to stress and continuing during a 14-day stress procedure. Controls were either untreated or treated with either of the two drugs. At the 1st after-stress week, sucrose preference, forced swim, novel cage, and fear-conditioning tests were carried out; the sucrose test and 5-day Morris water maze test followed by a sacrifice of mice on post-stress day 31 for all mice were performed. Transcriptome Illumina analysis of hippocampi was carried out. Using the RT-PCR, the hippocampal gene expression of Dhhc3, Dhhc7, Dhhc8, Dhhc13, Dhhc14, and Dhhc21 was studied. We found that chronic stress lowered sucrose preference in a subgroup of mice that also exhibited prolonged floating behavior, behavioral invigoration, and impaired contextual fear conditioning, while auditory conditioning was unaltered. At the remission phase, no changes in the sucrose test were found, and the acquisition of the Morris water maze was unchanged in all groups. In anhedonic, but not resilient animals, Dhhc8 expression was lowered, and the expression of Dhhc14 was increased. Antidepressant treatment with either drug partially preserved gene expression changes and behavioral abnormalities. Our data suggest that Dhhc8 and Dhhc14 are likely to be implicated in the mechanisms of depression at the remission stage, serving as targets for preventive therapy.